Production Indicators and Levels of Corticosterone in Pullets Treated with Beak-Trimming Protocols - Vieira, Ja; Garcia, Ea; Oba, E; Santos, Ta; Molino, Ab; Silva, Ap; Pelícia, K; Paz, Icla (Fundação APINCO de Ciência e Tecnologia Avícolas, 2018)
The aim of this study was to compare the effects of beak trimming by hot blade or infrared radiation on production indicators and plasma levels of corticosterone in pullets. During the rearing phase, an entirely random delineation was used a 2 x 3 factorial design (two different techniques for beak trimming x 3 strains), a total of six treatments with six repetitions of 20 hens. In the growing phase, the previous treatments were divided into 12, with eight repetitions with seven hens. These treatments were then distributed in a factorial design of 2 x 3 x 2 (two methodologies for beak trimming during rearing phase x three strains x with or without beak trimming at ten weeks of age). In the rearing phase the birds treated by infrared radiation had a lower total consumption and a longer beak length. In the growing phase, the execution of beak trimming at ten weeks of age, led to a lower total consumption and a lower body weight, but a better food conversion, when compared to those hens that did not have beak treatment. Beak trimming at ten weeks did not change the plasmatic levels of corticosterone.
Keywords: Beak treatment; infrared radiation; poultry production; stress; welfare.